The Mississippi encyclopedia / senior editors, Ted Ownby and Charles Reagan Wilson ; associate editors, Ann J. Abadie, Odie Lindsey, and James G. Thomas, Jr. ; sponsored by the Center for the Study of Southern Culture at the University of Mississippi. (2017)
Summary goes here